Peningkatan Pemahaman Keuangan Mahasiswa melalui Seminar Literasi Keuangan oleh KKN Universitas Alkhairaat Angkatan LVI : Penelitian - Fadliah. H. Al-Habsy; Abd. Fadlan; Adrian Lewer; Rosnita; Firna Sofia; Sadiah Alhaddar; Hairunnisa; Muhammad Nur Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) of Universitas Alkhairaat Batch LVI Group 104 carried out a flagship activity entitled Financial Literacy Seminar for Universitas Alkhairaat students. The seminar was held at the Faculty of Religion Auditorium and attended by 37 students from various study programs. The main objective of this seminar was to provide education about the importance of financial literacy among students to enable them to manage their personal finances wisely, intelligently, and productively. The method used an educative-informative approach through material presentation and interactive discussions. The results showed an improvement in participants’ understanding of basic financial literacy concepts, personal financial management, and awareness of saving and avoiding consumptive behavior. This activity is expected to serve as an initial step in strengthening the culture of financial literacy within the Universitas Alkhairaat academic community.